MATHEMATICS AND ENTRANCE EXAM RESULTS AS INDICATORS OF ACADEMIC SUCCESS AMONG CIVIL ENGINEERING STUDENTS - Ljubiša Preradović; Miroslav Malinović (AGG+)
It is crucial to select high-quality candidates for college and university enrollment, focusing on preparing them for their future careers in the shortest possible study duration while maintaining a strong graduation rate. The most reliable predictors of academic success (graduation) are observed during candidate testing (entry exams) and within the first year of study. This paper examines the factors influencing candidate enrollment in the Civil Engineering study program, including performance in mathematics (during the first year of study), the status of enrolled students, and the completion of their studies. It also explores the relationship between the study duration and academic performance in secondary school, the entry exam results, and the ability to predict academic success—graduation. The goals of the research were to analyze the success achieved during secondary education among SP CE students over the 12-year period, to research the success of students depending on the type of secondary school completed, qualification exam results, study status, passed mathematics courses that students study during the first academic year and to examine the possibility of using more advanced techniques for predicting the completion of studies